Spatial distribution and life‐history aspects of blackspot seabream Pagellus bogaraveo (Osteichthyes: Sparidae). Issue 6 (December 2013) - Mytilineou, Ch.; Tsagarakis, K.; Bekas, P.; Anastasopoulou, A.; Kavadas, S.; Machias, A.; Haralabous, J.; Smith, C. J.; Petrakis, G.; Dokos, J.; Kapandagakis, A.
<x xml:space="preserve">Abstract</x> Spatial distribution and life history aspects of Pagellus bogaraveo in the eastern Ionian Sea were investigated using the data from 13 different studies carried out in the area from 1983 to 2010. The spatial patterns of the abundance, biomass and mean size showed that the species inhabits the shallow waters of the shelf (<170 m depth) as juveniles up to a certain size (<180 mm total length, LT), moving to deeper waters of the slope (mainly 400–500 m depth) as adults. The spatial pattern of abundance indicated a continuous distribution of the species in deep waters, with hot‐spot areas of high values, whereas in shallow waters distribution was more discontinuous, with higher concentrations of juveniles in estuaries and brackish waters. The study of biological aspects of the species revealed (1) a difference in the increase in mass between males and females, (2) protandrous hermaphroditism, accompanied by the presence of primary females and males that do not change sex, (3) a sex ratio in favour of females >250 mm LT, (4) the presence of hermaphrodites between 200 and 370 mm, (5) a long reproduction period from June to March, (6) a size at first maturity around 300 mm and (7) a diet composition of adults based mainly on fishes, and also on opportunistic behaviour in the food scarce environment of deep waters. The results suggest that the species' distribution and feeding strategies are the most appropriate for the oligotrophic eastern Ionian waters and that these conditions result in smaller sizes of the species in the east Mediterranean Sea compared to the west basin and the east Atlantic Ocean, with implications for the growth and reproductive biology of the species.